Evaluating Parental Awareness Regarding the Children’s Visual Examination - İsmail Yıldız (Çocuk Dergisi)
Objective: Objective visual evaluation are an essential part of childhood check-ups. This study aims to evaluate parental awareness, attitudes, and behaviors regarding the children’s vision screening. Materials and Methods: The present study is a survey-based cross-sectional descriptive study. The data were obtained from questionnaires filled out by parents with children under six years of age. The study was conducted using data from 183 questionnaires. Results: Of the children, 53.6% (n = 98) are girls, 51.4% (n=94) have never had a vision examination/evaluation, and 82% (n=150) have been exposed to monitors. Of the parents, 44.3% (n=81) have vision problems. The median daily value of time exposed to digital screens is 2 hours, and the median value of exposure onset time is 12 months. The digital screen exposure rate in children under 18 months of age is 44.2%, with a median daily exposure time of 1 hour. While 87.1% of the parents of children who had not been previously examined by an ophthalmologist do feel their children should have regular visual evaluations, 89.7% had thought about visual evaluations for their children before they started school. Conclusion: Having family physicians inform parents about vision screenings, refer them to an ophthalmologist if necessary, and explain to parents that early exposure to digital screens in particular negatively affects children’s eye health will increase parents’ sensitivity to vision health.